HUBUNGAN KEBISINGAN DAN MASSA KERJA TERHADAP TERJADINYA STRES KERJA PADA PEKERJA DI BAGIAN TENUN AGUNG SAPUTRA TEX PIYUNGAN BANTUL YOGYAKARTA - Budiyanto, Tri; Pratiwi, Erza Yanti (Universitas Ahmad Dahlan, 2010)
Background : Work stress is a problem for the workers health and it is potential to increase the risk of working accident, cause psychological burden, physical load and it was able to decrease the productivity thoroughly. The influence of stress for long term, it is able too posses the certain consequences for the body. This research aim was know the relationship between the noises and work term with work stress to the weaving Agung Saputra Tex Piyungan, Bantul, Yogyakarta.Methods : This research was analytic observational using cross sectional approach. The research population is all workers of the weaving section Agung Saputra Tex Piyungan, Bantul, Yogyakarta. The technique of collecting sample was Totality Sampling method. The sample takes 40 peoples. Data analysis was performing univariate and bivariate.Result : The result of the research shown that was a significant correlation between the level of noise to the occurrence of work stress with p-value of 0,039 < alfa = 5% and the value of RP = 1,857 times (0,463 to 7,445) and there was a significant correlation between years of service to the occurrence of work stress with p-value of 0,019 < alfa = 5% and the value of RP = 1,459 times (0,654 to 3,259).Conclusion : All independent variable studied a meaningful relationship that were noise and years of service to the occurrence of work on worker stress weaving section Agung Saputra Tex Piyungan Bantul Yogyakarta.Keywords : Work stress, noise, and working period.